2011
DOI: 10.1097/ana.0b013e318225c979
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants of the ACE Gene and Aneurysmal Subarachnoid Hemorrhage in a Danish Population

Abstract: In this Danish population, ACE haplotypes and the I/D polymorphism did not contribute significantly to the overall risk of intracranial aneurysm rupture. Larger studies are needed to delineate the association between ACE polymorphism and ruptured middle cerebral artery aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Certain previous studies investigated the influence of ACE I/D gene polymorphisms on IA susceptibility (17)(18)(19)(20)(21)(22)(23); however, the results of these studies remain inconsistent. As a single study might not be powered to demonstrate the overall effects, Association between angiotensin-converting enzyme insertion/deletion polymorphisms and intracranial aneurysm susceptibility: A meta-analysis a meta-analysis using currently available data was performed in the present study to detect the potential association of ACE I/D gene polymorphisms on IA risk.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Certain previous studies investigated the influence of ACE I/D gene polymorphisms on IA susceptibility (17)(18)(19)(20)(21)(22)(23); however, the results of these studies remain inconsistent. As a single study might not be powered to demonstrate the overall effects, Association between angiotensin-converting enzyme insertion/deletion polymorphisms and intracranial aneurysm susceptibility: A meta-analysis a meta-analysis using currently available data was performed in the present study to detect the potential association of ACE I/D gene polymorphisms on IA risk.…”
Section: Introductionmentioning
confidence: 56%
“…Subsequently, various studies with conflicting opinions have been reported (18,19,23). A previous meta-analysis failed to detect an association between the ACE I/D polymorphism and IA susceptibility in the dominant (OR=1.23, 95% CI=0.82-1.85; P OR =0.31) or the recessive (OR=1.58, 95% CI=0.98-2.57; P OR =0.06) models (11).…”
Section: Codominant Model -------------------------------------------mentioning
confidence: 99%
“…A subpopulation of the participants were part of another genetic association study concerning the effects of the ACE I/D polymorphism, which found no association with SAH. 30 …”
Section: Participantsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] Finally, a total of six studies were included in our meta-analysis, which included 744 ICH cases and 1411 controls. [19][20][21][22][23][24] Study characteristics are summarized in Table 1. Of those, one study included population-based case-control studies, and five studies included hospitalbased case-control studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Through the step of screening the title and abstracts, 83 articles were excluded, leaving 15 articles for full publication review. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Of these, nine were excluded. [25][26][27][28][29][30][31][32][33] Finally, a total of six studies were included in our meta-analysis, which included 744 ICH cases and 1411 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%